Elaboração e caracterização de blendas biodegradáveis a base amido de milho com Polihidroxibutirato (PHB) - Flórez Cristancho, Jennifer Paola (2017)
The present work aims to study the effect of addition of polyhydroxybutyrate (PHB) as filler in thermoplastic corn starch (TPS) produced by thermal compressionmolded. Initially, the effect of different amounts of the plastificant glycerol (25, 30 and 35 wt%) was evaluated in the physico-chemical properties of TPS. After that, blends with 35 % glycerol and different PHB contents (10, 20 and 30 wt%) were prepared. Additionally, in this work the surface of the PHB granules was modified by plasma treatment using atmospheric air and sulfur hexafluoride (SF6) gas. In order to evaluate the influence of the PHB contents before and after the plasma treatment, the blends were characterized by FTIR, TGA, DSC, XRD, SEM and mechanical tests. The PHB granules showed a homogeneous distribution in the TPS matrix and the higher PHB contents presented an increase in the mechanical properties. On the other hand, the micrographs of the blends using plasma treated PHB showed agglomerates in the starch matrix, which represented stress concentrators, and showed weak interfacial adhesion related to the low mechanical strength and the small deformation at the break. The thermogravimetric analysis of the blends with PHB treated by plasma showed a higher thermal stability up to a loss of mass of 20 % when compared with blends of TPS and PHB without plasma treatment.